Calculation of Value at Risk of Property Fire Losses in West Jakarta with the Extreme Value Theory Method - Putri, Linda Damayanti (International Journal of Mathematics, Statistics, and Computing, 2025)
Property fires are an inevitable disaster, but their impact can be minimized through proper risk management. In urban areas such as West Jakarta, with high population density and economic activity, fires often cause losses. In therange of 2014 to 2023, the peak of the loss occurred in 2019 of IDR 103,354,500,000. Soto avoid unwanted things, it is necessary to calculate the losses that may occur. The Extreme Value Theory (EVT) method is used in this study to analyze the risk of extreme losses. Using Peaks Over Threshold (POT), the estimated value at Risk (VaR) shows a maximum loss of IDR 86,245,771,176 (95% confidence level) and IDR 255,535,153,859 (99% confidence level). These results help manage fire insurance risks to reduce future economic impacts.